Pluripotent-Stem-Cell-Derived Hepatic Cells: Hepatocytes and Organoids for Liver Therapy and Regeneration - Messina, Antonietta (Cells, 2020)
The liver is a very complex organ that ensures numerous functions; it is thus susceptible to multiple types of damage and dysfunction. Since 1983, orthotopic liver transplantation (OLT) has been considered the only medical solution available to patients when most of their liver function is lost. Unfortunately, the number of patients waiting for OLT is worryingly increasing, and extracorporeal liver support devices are not yet able to counteract the problem. In this review, the current and expected methodologies in liver regeneration are briefly analyzed. In particular, human pluripotent stem cells (hPSCs) as a source of hepatic cells for liver therapy and regeneration are discussed. Principles of hPSC differentiation into hepatocytes are explored, along with the current limitations that have led to the development of 3D culture systems and organoid production. Expected applications of these organoids are discussed with particular attention paid to bio artificial liver (BAL) devices and liver bio-fabrication.